PEMECAHAN MASALAH BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - EFRI - YENI (Jurnal Tunas Pendidikan, 2021)
This research is motivated by the fact in schools that mathematics learning is carried out by the teacher only with the flow of providing information, lectures, practice questions, and giving assignments, without being given the opportunity to find out on their own. Many approaches can be used to change the way teachers teach. The problem of this research is how to apply a contextual approach to improve the learning outcomes of story questions about FPB in class IV SD Negeri 05 / VIII Balai Rajo. While the use of this discussion is as a reference for teachers to use a contextual approach in mathematics learning, especially in problem solving learning. To arrive at the objectives and benefits of this study, a classroom action research was conducted. The research method was conducted using Classroom Action Research. The research procedure starts with planning, implementing, observing (observation), and reflecting. This research was conducted in two cycles, each cycle carried out two meetings. Each cycle carried out a contextual approach and proved that there was an increase in student learning outcomes in the material for solving story questions related to FPB and KPK at IV SD Negeri 05 / VIII Balai Rajo. It can be seen that student learning outcomes increased from the class average of 71.11 in the first cycle to 88.6 in the second cycle. There was also an increase in student activity in the first cycle, only 65 to 80 in the second cycle. This shows that contextual-based problem solving learning can improve student learning outcomes and activities.